Particle size distribution measurement from different indoor activities - Aui, Shwu Harn (2015)
Human exposure to particulate matter can have significant harmful effects on the respiratory and cardiovascular system. These effects vary with number, size, and chemical composition of particulate matter. Studying the particle size distribution under different indoor activities can help to predict the emission and settlement of particles with different sizes. In this research, an experimental study was carried out to investigate the particle size distribution under different indoor activities in main office FTeK and OSHMO. The indoor activities of office being studied were printing, photocopying and use of air freshener sprays. Data collection was done by using laser light scattering instrument to measure the number concentration of particles ranging from 0.3 μm to 10 μm. Then, the particle size distribution graph for each activity was generated using the particle number concentration measured and particle size range. Environmental parameters such as temperature, relative humidity, air velocity were measured using IAQ meter. Air change rate was measured using Concentration Decay Test Method (ASTM Standards E741-00). From the result obtained, the particle size distribution of printing, photocopy and use of freshener spray was ranged from 0.3 μm to 10 μm, with the predominant size range of 0.3 μm - 0.5 μm. The use of air freshener has the highest emission rates which are 3.73 x 1010 s-' at FTeK and 2.97 x 1010 s at OSHMO. Whereas printing has the lowest emission rates, which are 3.92 x 1010 s at FTeK and 2.63 x 1010 s at OSHMO. Significant elevation of indoor particle concentration was noted during the three activities. The photocopy activity can be the major source of indoor particle concentration because it emitted high number concentration of particles within a short period and the particles remain fluctuated in the indoor air with slow decay rate. In conclusion, the three activities selected produced high level of submicrometer particles (< 1 μm) and indoor particle concentration is mainly associated with the indoor activities.